Mobile web-based student portal with qr code for school digitalization - Adham Ghilbran Alyora; Adam Sekti Aji (Institute of Computer Science (IOCS), 2026)
The mobile web-based Student Portal application utilizing QR Barcode technology was developed as a solution to limited access and low efficiency in managing student data within schools. Without the support of this system, processes such as attendance, academic information delivery, and communication between students and educators tend to be slow and prone to recording errors, ultimately affecting the effectiveness of learning and school administration. To address these challenges, a user needs analysis was conducted, an adaptive interface design was created to support various devices (responsive), and QR code scanning was integrated to facilitate attendance and digital access to information. The application development process followed an iterative method, actively involving users during testing stages to obtain relevant feedback. Preliminary results indicate that the implementation of this application can enhance student data management efficiency, accelerate communication between students and school staff, and support the creation of a more modern, interactive, and integrated learning environment.